Varicella Zoster Virus Infections in Canadian Children in the Prevaccine Era: A Hospital-Based Study - Susan Kuhn; H Dele Davies; Taj Jadavji (Canadian Journal of Infectious Diseases)
OBJECTIVE: To describe the clinical course of children admitted for varicella zoster virus (VZV) infections to a pediatric hospital before the release of VZV vaccine in Canada.